FRI0684 NOVEL MAPPING FUNCTION ILLUSTRATES NONLINEARITY BETWEEN TRIAL ACR RESPONSE, DAS28 CHANGE AND EULAR RESPONSE CRITERIA. (June 2019) - Coy, Nuria Navarro; Hyrich, Kimme; Pavitt, Sue; West, Robert; Buch, Maya
Abstract : Background: The American College of Rheumatology (ACR) definition of improvement is a standardised, widely used outcome measure for clinical trials in rheumatoid arthritis. In routine clinical practice (and registries), improvement is assessed by the DAS28 (Disease Activity Score 28), particularly in the UK, where it is the basis of current NICE guidance 1 . Objectives: To develop a mapping function that charts ACR20/50/70 and ACRn to ΔDAS28 and EULAR response, and determine the relationship between the response measures. Methods: Individual patient-level data from the 428 participants randomised to the ATTRACT 2 trial were used. The proportion of participants with ACRn (ACR10-ACR90) response and the change in DAS28 (ΔDAS28) at 30 weeks from baseline were calculated and analysed analysed in participants with complete data. The cut points in ΔDAS28 that provided the equivalent proportion of participants achieving ACR10 to ACR90 at 30 weeks overall and per individual arm were searched for through tabulation. Regression models were conducted and misclassification rates calculated to test the accuracy of the mapping function. The minimum and maximum ACRn achieved per EULAR response category were also determined to establish the correlation of these two response criteria. R version 3.4.3 (2017-11-30) was used for all statistical analyses. Results: 53%/27%/12% of all trial participants achieved ACR-ESR 20/50/70 responses, respectively. The mapping function shows that at 30 weeks a 20% improvement in ACR is equivalent to a 27.3% and 27.8% improvement from baseline in DAS28 calculated using ESR and CRP, respectively. 50% improvement in ACR is equivalent to a 45% and 46.2% improvement in DAS28-ESR and DAS28-CRP, respectively. 70% improvement in ACR is equivalent to a lower improvement in the DAS28, at 55.8% for ESR and 59.3% for CRP. Similar results were obtained when analysing the individual arms (Table 1 & Figure 1 ). Baseline DAS28 for all analysed groups was ≥ 6.0. Moderate or good EULAR responses correspond to 80% and 90% improvement in ACR, respectively, whereas the no response EULAR category showed a maximum improvement in ACR-ESR/CRP of 30%-50%, respectively (Figure 2 ). Conclusion: This novel mapping function enables the comparison of trials reporting ACR20/50/70 with those reporting ΔDAS28. The results imply nonlinearity in the relationship between ACR20/50/70, ΔDAS28 and EULAR response criteria. Limitations: The mapping is dependent on the population chosen to examine it, which in this analysis comprised trial participants with very active disease. References: [1] National Institute for Health and Care Excellence (NICE), Technology Appraisal Guidance (TA375) 2016. 2Maini R, et al. Lancet 1999. Disclosure of Interests: Nuria Navarro Coy: None declared, Kimme Hyrich Grant/research support from: Grants to institution: BMS, Pfizer, UCB, Sue Pavitt: None declared, Robert West: None declared, Maya Buch Grant/research support from: Pfizer LTD, UCB, Consultant for: AbbVie, Eli Lilly, EMD Serono, Pfizer Ltd., Sanofi